GAMBARAN PENGETAHUAN, SIKAP, DAN TINDAKAN PENGOBATAN SENDIRI PADA PASIEN DI PUSKESMAS SUKARAMAI MEDAN - NELLI MURLINA; RIJENA KARINA ABIGAEL BANGUN (JURNAL ILMIAH KOHESI, 2022)
Self-medication or self-sufficiency is the selection and use of drugs by individuals to treat a self-recognized disease orsymptom. Basic Health Research 2013 in Indonesia reported a total of 103,860 (35%) of the 294,959 households stored thedrug for self-treatment. Self-medication can be a source of medication error due to limited public knowledge. This study aimsto find out the picture of self-medication in patients at Sukaramai Medan health center. Descriptive research with a "crosssectional"research design. Data retrieval is done by interview technique using questionnaire instruments. Data analysisusing the SPSS (Statistical Product and Service Solutions) program. The majority of respondents' knowledge level of selftreatmentwas moderate, which was 60 (61.2%) respondents. The majority of respondents' attitudes towards self-medicationwere moderate, with 83 (85.6%) respondents. The majority of respondents' actions against self-treatment were moderate,with 45 (45.9%) respondents. The majority of the respondent's knowledge level, attitude, and actions towards self-medicationwere moderate.